Protection Of The Constitutional Rights of Indonesian Migrant Workers Abroad Post-Placement In Destination Countries - Ahmad; Agus Muhidin; Gamal Abdul Nasir (Universitas Muhammadiyah Surabaya, 2025)
This study describes the protection of constitutional rights of Indonesian migrant workers after being placed in destination countries. Migrant workers often face various challenges, including exploitation, discrimination, and violence. This research highlights the protection efforts undertaken by the Indonesian government and international organizations to ensure the fulfilment of migrant workers' rights in accordance with the constitution. The main focus is on policy implementation, bilateral agreements, and multilateral cooperation aimed at improving the conditions and protection of migrant workers. Research methods include policy analysis, case studies, and interviews with migrant workers and relevant stakeholders. Key findings include challenges in policy implementation, the need for improvements in the protection system, and the importance of advocacy and awareness of rights as part of long-term solutions. This study makes a significant contribution to understanding the protection of constitutional rights of Indonesian migrant workers abroad and offers policy recommendations to enhance their protection in the future.